Development and Evaluation of a Visual Novel Game “Happiness” to Introduce the 5 Stages of Grief - Lumombo, Liony; Pertiwi, Annisa (Jurnal Pendidikan Multimedia (Edsence), 2024)
Grieving is a feeling intimately associated with sadness and loss, and as a fundamental aspect of the human experience, it is an inevitable component of life. In the context of bereavement, individuals typically traverse the five stages of grief before achieving a state of equilibrium. However, the societal under-appreciation of these stages often engenders a prolonged and unresolved grief response, underscoring the necessity for educational initiatives that promote awareness of these stages. Visual game novels, a medium that employs narrative and visual elements to illustrate the stages of grief, offer a valuable avenue for conveying these concepts. These novels utilize Ren'py, a software application designed for creating visual novels, to present image illustrations alongside a narrative. In addressing this gap in understanding, the researcher developed a visual game novel titled "Happiness," which serves as an introduction to the five stages of grief. To gather data for this study, the researcher employed qualitative methods, conducting in-depth interviews using judgmental sampling techniques. The findings of this study contribute to the development of innovative educational media, particularly in the context of understanding the grieving process. Subsequent research can be conducted to generalize the findings to a broader population and explore the potential for cultural adaptation in game design.